Mortality predictors in a cohort of patients with COVID-19 admitted to a large tertiary hospital in the city of São Paulo, Brazil - Oliveira, Regina Maria Alexandre Fernandes de; Gorzoni, Milton Luiz; Rosa, Ronaldo Fernandes (São Paulo Medical Journal, 2023)
BACKGROUND: There is discrepant information across countries regarding the natural history of patients admitted to hospitals with coronavirus disease (COVID-19), in addition to a lack of data on the scenario in Brazil. OBJECTIVE: To determine the mortality predictors in COVID-19 patients admitted to a tertiary hospital in São Paulo, Brazil. DESIGN AND SETTING: A retrospective analysis of medical records of COVID-19 patients admitted to the Hospital Central da Irmandade da Santa Casa de Misericórdia of São Paulo. METHODS: Overall, 316 patients with laboratory-confirmed COVID-19 between March 1, 2020, and July 31, 2020, were included. The analysis included the baseline characteristics, clinical progression, and outcomes. RESULTS: The mortality rate of the sample was 51.27%. Age ≥ 60 years was determined as a risk factor after multivariate logistic regression analysis. Patients with an oxygen (O2) saturation ≤ 94% upon admission accounted for 87% of the deaths (P < 0.001). Vasoactive drugs were used in 92% (P < 0.001) of patients who progressed to death, and mechanical ventilation was employed in 88% (P < 0.001) of such patients. However, patients who received corticosteroids concomitantly with mechanical ventilation had a better prognosis than those who did not. The progressive degree of pulmonary involvement observed on chest computed tomography was correlated with a worse prognosis. The presence of thrombocytopenia has been considered as a risk factor for mortality. CONCLUSION: The main predictors of in-hospital mortality after logistic regression analysis were age, O2 saturation ≤ 94% upon admission, use of vasoactive drugs, and presence of thrombocytopenia.